Epigenetics, estradiol, and hippocampal memory consolidation - Frick, Karyn M. (2013)
Epigenetic alterations of histone proteins and DNA are essential for hippocampal synaptic plasticity and cognitive function, and contribute to the etiology of psychiatric disorders and neurodegenerative diseases. Hippocampal memory formation depends on histone alterations and DNA methylation, and increasing evidence suggests that regulation of these epigenetic processes by modulatory factors such as environmental enrichment, stress, and hormones substantially influences memory function. Recent work from our laboratory suggests that the ability of the sex-steroid hormone 17β-estradiol (E(2)) to enhance novel object recognition memory consolidation in young adult female mice is dependent on histone H3 acetylation and DNA methylation in the dorsal hippocampus. Our data also suggest that enzymes mediating DNA methylation and histone acetylation work in concert to regulate the effects of E(2) on memory consolidation. These findings shed light on the epigenetic mechanisms that influence hormonal modulation of cognitive function, and may have important implications for understanding how hormones influence cognition in adulthood and aging. This review will provide a brief overview of the literature on epigenetics and memory, describe in detail our findings demonstrating that epigenetic alterations regulate E(2)-induced memory enhancement in female mice, and discuss future directions for research on the epigenetic regulation of E(2)-induced memory enhancement.